Edukasi Stunting pada Masyarakat untuk Mencegah dan Menanggulangi Stunting di Desa Tegalombo Kecamatan Kalikajar Kabupaten Wonosobo - Prehatiningtias, Era Tunggal; Devi Yonifasari, Chrisna; Rahmawati, Erika; Valek Stefani, Adiella; Nur Auliasari, Irni (Universitas Negeri Semarang, 2023)
Stunting is a condition of failure to thrive and a problem of malnutrition in children whose basic nutrition is inadequate. Stunting is caused by many factors, namely malnutrition, diseases suffered by pregnant women, and parental factors (parenting style and economy). Stunting cases in Wonosobo Regency are more common in girls than boys. Stunting education held by GIAT 3 UNNES students in Tegalombo Village to make people aware of the dangers of stunting, prevent and overcome stunting. The method used is deformation teaching using subjects, lectures and group discussions with the help of PowerPoint media and guides. Prevention of stunting can be done by providing healthy and nutritious nutrition according to age category and socializing stunting in the community. Stunting prevention is carried out through a balanced nutritional diet, clean living, proper parenting, exclusive breastfeeding for babies aged 0 - 6 months, and MPASI for babies over 6 months - 2 years.